Enhanced CO2 Capture Performance Using Methyl Diethanolamine-functionalized Silica Gels: Assessing CO2 Capture Capacity - Petpitcha Boonmatoon; Pacharapol Nokpho; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (Applied Environmental Research)
Carbon dioxide (CO2) is a significant greenhouse gas. This causes harm to the environment and to humans. In 2023, atmospheric CO2 levels rose to 420 ppm, marking a new record high. Therefore, technology for capturing CO2 has been developed. At present, a wide variety of technologies have been proposed to capture CO2. Adsorption technology is more affordable and requires less energy for regeneration. There are many potential solid adsorbents for CO2 capture, such as zeolites, alumina, metal‒organic frameworks (MOFs), and mesoporous silicas. Silica materials possess unique properties that make them promising candidates as solid sorbents for CO2 capture. They provide several benefits, such as high adsorption capacity under dry conditions at ambient temperature, along with low energy requirements for regeneration. Amine-functionalized silica adsorbents are among the most promising methods for CO2 capture, offering high efficiency and high uptake rates. In this study, silica gels were grafted and impregnated with amines via methyl diethanolamine (MDEA). The effects of water content and amine loading on CO2 capture performance were investigated. The MDEAs grafted and impregnated on silica gel exhibited excellent CO2 efficiencies of 0.36 and 0.38 mg CO2 per gram sorbent, respectively, which are higher than the 15% efficiency of the unmodified adsorbent. The results showed that the modified silica gel had high CO2 efficiency during the first three adsorption‒regeneration cycles when the water content and amine loading increased. Moreover, the nitrogen content increased with increasing water content, leading to an increase in the adsorption capacity.